Pengetahuan ibu Balita tentang gizi dan pola pemberian makan dengan status gizi Balita - Hariza Adnani; Kiki Kandi Rettob (Health Sciences and Pharmacy Journal, 2023)
The results of a preliminary study in Srimulyo Village, Working Area of the Piyungan Bantul Health Center, 3 out of 5 mothers of toddlers only provide food that their children like, such as snacks. These foods lack the nutrients children need. The purpose of this study was to determine the relationship between mother's knowledge about nutrition and feeding patterns with the nutritional status of toddlers. This research is a quantitative analytic research with cross sectional research methods. The population in this study were all mothers who have toddlers in Srimulyo Village, the working area of the Piyungan Bantul Health Center. In taking samples using probability sampling technique with random sampling type. Data were analyzed using the chi-square test and Kendall's tau test. The results of the chi-square test showed that there was a relationship between mother's nutritional knowledge and toddler's nutritional status (p value = 0.032 0.05) and there was a relationship between eating pattern and toddler's nutritional status (p value = 0.031 0.05). The conclusion from this study is that mothers' knowledge about nutrition and feeding patterns are related to the nutritional status of toddlers in Srimulyo Village, the working area of the Piyungan Bantul Health Center in 2022.